Experimental and numerical studies on propagation behavior between hydraulic fractures and pre-existing fractures under prepulse combined hydraulic fracturing - Chao Wei; Liyuan Yu; Shentao Geng; Zichen Yuan; Yubo Wang (Journal of Rock Mechanics and Geotechnical Engineering)
Prepulse combined hydraulic fracturing facilitates the development of fracture networks by integrating prepulse hydraulic loading with conventional hydraulic fracturing. The formation mechanisms of fracture networks between hydraulic and pre-existing fractures under different prepulse loading parameters remain unclear. This research investigates the impact of prepulse loading parameters, including the prepulse loading number ratio (C), prepulse loading stress ratio (S), and prepulse loading frequency (f), on the formation of fracture networks between hydraulic and pre-existing fractures, using both experimental and numerical methods. The results suggest that low prepulse loading stress ratios and high prepulse loading number ratios are advantageous loading modes. Multiple hydraulic fractures are generated in the specimen under the advantageous loading modes, facilitating the development of a complex fracture network. Fatigue damage occurs in the specimen at the prepulse loading stage. The high water pressure at the secondary conventional hydraulic fracturing promotes the growth of hydraulic fractures along the damage zones. This allows the hydraulic fractures to propagate deeply and interact with pre-existing fractures. Under advantageous loading conditions, multiple hydraulic fractures can extend to pre-existing fractures, and these hydraulic fractures penetrate or propagate along pre-existing fractures. Especially when the approach angle is large, the damage range in the specimen during the pre-pulse loading stage increases, resulting in the formation of more hydraulic fractures.